Anita Roddick - a tough act to follow - Abd Razak, Dzulkifli (2007)
IN almost every hotel room that you check in, there will be a "Dear Guest" message hanging in the bathroom. It will read: "Please help us preserve the environment by hanging up any towels you intend to reuse." Somehow it is too towelcentred. No mention is made about the judicious use of water or electricity, especially the use of central airconditioning. Or whether the soap, shampoo or bath gel supplied are environmentfriendly. Then there's the complimentary "natural" mineral water in a plastic bottle—knowing full well what plastic bottles can do to the environment. In other words, hoteliers could do much more for the environment, if they are genuinely interested. After all, there are numerous environmentfriendly items in the market.